How to use Google Docs, sheets, slides and drive (Que, 2015)
"Get super-productive with Google's online applications-painlessly! Using Google Docs, Sheets, Slides, and Drive puts all the power of Google's apps at your command, even if you've never used any of them! In just 5 1/2 hours of incredibly easy video, Michael Miller gets you 100% comfortable and amazingly productive with Google's powerful online applications...just watch! Within minutes, you'll discover how Google's cloud-based apps work, how to get started, and how to create, import, export, save, and share files on any computer, smartphone, or tablet. Next, you'll master Google Docs' powerful text editing and formatting tools, so you can create powerfully effective documents and share them with anyone. Miller shows how to build great Google Sheets spreadsheets for personal finance and other tasks...create and deliver highly effective presentations with Google Slides...and make the most of free or low-cost Google Drive storage wherever you go. More than 50 million people already use Google Apps: It's today's #1 new productivity tool. This complete video tutorial teaches you all the skills you need to join them, fast!"--Resource description page.